2021
DOI: 10.4103/ijnmr.ijnmr_228_19
|View full text |Cite
|
Sign up to set email alerts
|

Cold Therapy and Respiratory Relaxation Exercise on Pain and Anxiety Related to Chest Tube Removal

Abstract: Background: Current strategies to control pain and anxiety of chest tube removal are not efficacious. The aim of this study is to determine the effects of cold therapy and respiratory relaxation exercise on pain and anxiety of chest tube removal. Materials and Methods: A parallel single-blind clinical trial study was conducted in Imam Khomeini Hospital, Iran, on 120 patients. Participants were randomized into 4 groups of 30. Numeric Rating Scale was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…The results of the meta-analysis show that cold application can effectively reduce immediate pain intensity after CTR. This result is similar to those from the two studies conducted by Sajad et al [20] and Ertug and Ulker [24], respectively. In addition to pain relief after CTR, cold application was also reported to reduce pain before arterial puncture and intramuscular injection, but few studies have been reported [25,26].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of the meta-analysis show that cold application can effectively reduce immediate pain intensity after CTR. This result is similar to those from the two studies conducted by Sajad et al [20] and Ertug and Ulker [24], respectively. In addition to pain relief after CTR, cold application was also reported to reduce pain before arterial puncture and intramuscular injection, but few studies have been reported [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…Among the studies, 5 studies (50%) were rated as having a low risk of bias for random sequence generation because they were randomly employed using random number generators, random number tables, block randomization, eight-member block randomization, or computer programs [7,8,[19][20][21], and 5 studies were rated as having an unclear risk of random sequence generation [3,4,[22][23][24]. One study was rated as having an unclear risk of concealment because the author did not provide a detailed explanation [8], and 9 studies (90%) were rated as having high risks of allocation concealment [3,4,7,[19][20][21][22][23][24].…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations